Evolving wildlife management cultures of governance through Indigenous Knowledges and perspectives - Fisk, Jonathan James; Leong, Kirsten Mya; Berl, Richard E. W.; Long, Jonathan W.; Landon, Adam C.; Adams, Melinda M.; Hankins, Don L.; Williams, Christopher K.; Lake, Frank K.; Salerno, Jonathan (The Journal of wildlife management, 2024)
Within governance agencies, academia, and communities alike, there are increasing calls to recognize the value and importance of culture within social‐ecological systems and to better implement Indigenous sciences in research, policy, and management. Efforts thus far have raised questions about the best ethical practices to do so. Engaging with plural worldviews and perspectives on their own terms reflects cultural evolutionary processes driving paradigm shifts in 3 fundamental areas of natural resource management: conceptualizations of natural resources and ecosystems, processes of public participation and governance, and relationships with Indigenous Peoples and communities with differing worldviews. We broadly describe evolution toward these paradigm shifts in fish and wildlife management. We then use 3 case studies to illustrate the ongoing cultural evolution of relationships between wildlife management and Indigenous practices within specific historical and social‐ecological contexts and reflect on common barriers to appropriately engaging with Indigenous paradigms and lifeways. Our case studies highlight 3 priorities that can assist the field of wildlife management in achieving the changes necessary to bridge incommensurable worldviews: acknowledging and reconciling historical legacies and their continued power dynamics as part of social‐ecological systems, establishing governance arrangements that move beyond attempts to extract cultural information from communities to integrate Indigenous Knowledges into dominant management paradigms, and engaging in critical reflexivity and reciprocal, accountable relationship building. Implementing these changes will take time and a commitment to processes that may initially feel uncomfortable and unfamiliar but have potential to be transformative. Ethical and culturally appropriate methods to include plural and multivocal perspectives and worldviews on their own terms are needed to transform wildlife management to achieve more effective and just management outcomes for all. Transforming wildlife management institutions at the cultural level to increase alignment with diverse worldviews can improve relations with Indigenous Peoples and the implementation of Indigenous Knowledges within management. 3 priorities to facilitate this cultural shift are: reconciling historical legacies and power imbalances, moving beyond attempts to integrate Indigenous Knowledges into dominant management paradigms, and building reciprocal, accountable relations with Indigenous Peoples.